Pendidikan Karakter dalam Islam - Firman Amir; Leny Ms Tomagola (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of Islamic education is essentially to shape the character of students to develop as generations of "khaerah ummah", faithful and pious, mature in attitude and Islamic character, having independent thinking and spirit, creative, dynamic, and having noble character. Character education in Islam is very important, because the main task of the Prophet Muhammad was sent on this earth to improve the morals or character of mankind. So that the Prophet Muhammad is the main example of the example that Allah has given to Muslims throughout the universe. In Islam there are three main values, namely morality, adab, and example. Morals refer to duties and responsibilities other than sharia and Islamic teachings in general. While the term adab refers to attitudes associated with good behavior. And exemplary refers to the quality of character displayed by a good Muslim who follows the example of the Prophet Muhammad. These three values ​​are the pillars of character education in Islam